Experiences in Space. An Italian Triptych - Salmin, Leonid (project baikal, 2018)
Thinking about the feeling of interior of the urban environment, we refer to the emotional experiences of space, where interaction between a human being and a city is like an emotional coexistence. The human being is in the center of a special energy field archetypically experienced as HOME. A human body and an urban body make up a firm integration, the deep senses of which are inevitably manifested in everyday practices of urban life.